Decoding positron emission tomography–computed tomography avidity in prostate cancer: Why metastases light up brighter than the primary tumor: A case-based insight - Giddi, Mauryakrishna; Parashar, Eresh; Dey, Treshita (Indian Journal of Case Reports, 2026)
Prostate cancer is one of the most common malignancies affecting men worldwide, with a substantial proportion presenting with or eventually developing metastatic disease. Molecular imaging using positron emission tomographycomputed tomography, particularly with prostate-specific membrane antigen (PSMA)–based tracers, has significantly improved the detection and characterization of metastatic prostate cancer. We report the case of a 67-year-old male with high-risk prostate adenocarcinoma in whom metastatic lesions demonstrated markedly higher PSMA avidity than the primary tumor. This case highlights the biological heterogeneity between primary and metastatic disease, discusses the implications of differential tracer uptake on staging and treatment planning, and reviews relevant literature to explain this phenomenon.